Home range and movements of roof rats (Rattus rattus) in an old-growth riparian forest, California - Desley Whisson; JH Quinn; KC Collins (2007)
Information on the spatial ecology of nonnative roof rats (Rattus rattus) is important for developing management strategies to reduce their impacts on native wildlife in riparian habitats. We determined home-range size and movement patterns of nonnative roof rats (Rattus rattus) in an old-growth riparian forest in California by radiotracking 12 individuals in August and September 2002. Males had larger home ranges than females. There was considerable overlap of ranges within and between sexes. Rats nested from 2 to 15 m high in trees, and used multiple nests that were sometimes shared simultaneously with other rats. Rats were most active at night, spending most of their time on, or close to the ground, and favoring areas of dense cover of blackberry and grape.